SYNTHESIS, IN VITRO ANTIBACTERIAL, TOXICITY AND MOLECULAR DOCKING ANTICANCER ACTIVITY OF NOVEL N-[(2-CHLOROQUINOLIN-3-YL) METHYLIDENE]-2-ANILINE SCHIFF'S BASES - S., Pradeep P.; T. O., Shrungesh Kumar; N., Prashantha; M., Mahadevan K. (International Journal of Current Pharmaceutical Research, 2015)
Objective: Synthesis of N-[(2-chloroquinolin-3-yl) methylidene]-2-aniline schiff bases (3a-j) and to study their in vitro antibacterial activity and in silico study towards cancer and malarial proteins. Methods: Various N-[(2-chloroquinolin-3-yl) methylidene]-2-aniline schiff bases (3a-j) were synthesized by using 2-chloro-3-formyl quinoline and different anilines in presence of acetic acid as catalyst. All the new compounds were characterized by 1H-NMR, [13]C-NMR and LCMS analysis. The compounds 3a-j was subjected to antibacterial activity. In silico molecular properties were predicted using various online cheminformatic tools, the binding interactions with Human DNA topoisomerase I and Plasmodium falciparum lactate dehydrogenase proteins was studied through molecular docking and Irinotecan and mefloquine were used as reference drugs. Results: Fairly good yield of N-[(2-chloroquinolin-3-yl) methylidene]-2-aniline schiff bases (3a-j) were synthesized by convenient and economical procedure. The preliminary in silico pharmacokinetics study reveals that the compounds 3a-j shows excellent drug like property. The toxicity profile of compounds 3a-h was found safe. The compounds 3a-j was exhibited promising MIC values against the both S. aureus and E. coli. Similarly the docking results predict that the compound 3d shown highest interaction by forming two hydrogen bonds against the cancer protein with the interaction energy-20.696 kcal/mol. Compound 3c exhibits highest dock score of-45.703 kcal/mol with two hydrogen bonds against malarial protein. Conclusion: From the results of docking studies of N-[(2-chloroquinolin-3-yl) methylidene]-2-aniline schiff bases (3a-j), it has been concluded that the compounds were found to exhibit multifunctional lead property, hence these compounds are worth to be considered as potential lead molecules for further study.